Induction of Early Autophagic Process on Leishmania amazonensis by Synergistic Effect of Miltefosine and Innovative Semi-synthetic Thiosemicarbazone - Scariot, Débora B.; Britta, Elizandra A.; Moreira, Amanda L.; Falzirolli, Hugo; Silva, Cleuza C.; Ueda-Nakamura, Tânia; Dias-Filho, Benedito P.; Nakamura, Celso V. (Frontiers in Microbiology, 2017)
Drug combination therapy is a current trend to treat complex diseases. Many benefits are expected from this strategy, such as cytotoxicity decrease, retardation of resistant strains development and activity increment. This study evaluated in vitro combination between an innovative thiosemicarbazone molecule – BZTS with miltefosine, a drug already consolidated in the leishmaniasis treatment, against Leishmania amazonensis. Cytotoxicity effects were also evaluated on macrophages and erythrocytes. Synergistic antileishmania effect and antagonist cytotoxicity were revealed from this combination therapy. Mechanisms of action assays were performed in order to investigate the main cell pathways induced by this treatment. Mitochondrial dysfunction generated a significant increase of reactive oxygen and nitrogen species production, causing severe cell injuries and promoting intense autophagy process and consequent apoptosis cell death. However, this phenomenon was not enough strong to promote dead in mammalian cell, providing the potential selective effect of the tested combination for the protozoa. Thus, the results confirmed that drugs involved in distinct metabolic routes are promising agents for drug combination therapy, promoting a synergistic effect.